Recommendations of the Polish Society of Physiotherapy, Polish Society of Family Medicine and the College of Family Physicians in Poland in the scope of physiotherapy in the painful shoulder syndrome in primary healthcare - Kassolik, Krzysztof; Rajkowska-Labon, Elżbieta; Tomasik, Tomasz; Gieremek, Krzysztof; Dobrzycka, Anna; Andrzejewski, Waldemar; Kiljański, Marek; Kurpas, Donata (Family Medicine & Primary Care Review, 2018)
The objective of these guidelines in the scope of physiotherapy in primary healthcare is to suggest simple, uncomplicated and more cost-effective physiotherapeutic activities in patients experiencing pain due to painful shoulder syndrome. A general practitioner should decide whether the treatment undertaken within primary healthcare, including the process of physiotherapy, is effective and sufficient, or whether it requires more advanced activities, such as advanced diagnostics and further specialist treatment. The authors of the recommendations, apart from massage, also include procedures in the scope of kinesiotherapy, physiotherapy and orthopedic equipment. According to the authors, the aim of recovering the correct spatial system, called structural homeostasis, in the shoulder girdle, is, first of all, normalization of muscle tension and then inclusion in a rehabilitation program covering the methods to recover and consolidate the correct models of motor activity. The starting point for determining a rehabilitation program should be the ability to prepare a simple assessment of the patient’s condition. This may result from a palpation examination to determine the incorrect distribution of resting tension in the area of the muscles and tendons engaged in the pathology and causing pain. The authors believe that such a solution contains the key to reducing the costs of treatment, providing access to physical therapists and quick assistance in the scope of improvement of a patient’s clinical condition. At the same time, they emphasize the need to correct the previous healthcare model, so that it becomes a more effective tool in maintaining health.